PENGEMBANGAN MULTIMEDIA PEMBELAJARAN FISIKA TERINTEGRASI DENGAN PERSIAPAN PENGEMASAN PERANGKAT PEMBELAJARAN DI SMA - Sinaga, Reza Audina; Nasir, Muhammad; M. Syafi’i, M. Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to produce a multimedia physics learning integrated with packing preparation of learning tools in senior high school in valid. This research method used is Research and Development (R & D) with ADDIE’s model. Method steps include analysis, design, development, implementation and evaluation. Data collection was done through multimedia validation sheet by 6 validators, consisted of 3 persons expert and 3 persons expert users. The instrument of learning device validity developed consisted of aspect of planning, pedagogic, content and technique. The result of multimedia validation in aspect of planning got the average mark was 4.52 with high category, aspect of pedagogic is 4.53 with high category, aspect of content is 4.54 with high category and aspect of technique is 4.52 with high category. In conclusion, multimedia in this reaserch was declared valid and feasible to use as physics learning media for senior highschool on material of rectilinear motion. As recommendation, multimedia can be refined with following the times and doing the practicality test to school.Keywords : Multimedia, packing preparation of learning tools, rectilinear motion